Contribuição da amplitude de movimento articular do joelho na marcha de crianças com paralisia cerebral espástica - Batistela, Rosangela Alice [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Individuals with spastic cerebral palsy show muscle weakness, difficulties in the control of agonist and antagonist muscles, decreased range of motion and tonus and sensibility alterations, especially in knee joint. These problems can interfere on the performance of functional activities such gait. The aim of this study was to analyze the contribution of knee range of motion on gait of hemiplegic and diplegic children considering their asymmetries. Twelve children, 6 hemiplegics e 6 diplegics from 7 to 12 years of age (age average= 9,5 ± 1,93) took part. Spasticity was assessed by the Ashworth’s Modified Scale and the passive knee range of motion by an eletrogoniometer. The task was to walk on a walkway of 8m long, in their preferred speed, in 6 attempts, been 3 on right and 3 on left sagital planes. Eigth passive markers were bilaterally fixed for the kinematic record. Orthogonally to the walkway, two digital camcorders were assembled on the sagital plane. The fotogrametric procedures were performed by the Dvideow 6.3 software. The Matlab 7.0.1 software was used to filter and to calculate the dependent variables. The U test of Mann- Whitney found differences to the cerebral palsy type for knee extension/hiperextension (U = - 2.943; p= 0.003), knee relative angle at heel contact (U = - 5.992; p= 0.001) and knee range during stride (U = - 4.099; p= 0.001). The Wilcoxon’s test revealed differences according to the asymmetries for the hemiplegics only for the knee relative angle at heel contact (T= - 2.635; p<0.008). The contributions of passive knee range of motion, revealed by the Spearman correlations, for the more afected limb of the diplegics, showed that the knee extension/hiperextension interfere on the cadence, stride duration and step width; the knee relative angle at heel contact change the stride length and duration and cadence; and the...(Complete abstract click electronic access below)

Indivíduos com paralisia cerebral espástica apresentam fraqueza muscular, dificuldades no controle entre as musculaturas agonista e antagonista, restrição da amplitude de movimento e alterações do tônus e de sensibilidade, em especial na articulação do joelho. Tais alterações podem interferir no desempenho de atividades funcionais, incluindo a marcha. O objetivo deste estudo foi analisar a contribuição da amplitude de movimento articular do joelho no andar de crianças hemiplégicas e diplégicas considerando o hemicorpo. Participaram deste estudo 12 crianças com idade entre 07 e 12 anos (9,5 ± 1,93), sendo 6 hemiplégicas e 6 diplégicas. Espasticidade foi mensurada pela Escala Modificada de Ashworth e a amplitude de movimento passiva do joelho pelo eletrogoniômetro. A tarefa consistia em percorrer uma passarela de 8m, na velocidade preferida, em 6 tentativas, sendo 3 para o plano sagital direito e 3 para o plano sagital esquerdo. Para registro cinemático, 8 marcadores passivos foram fixados bilateralmente. Ortogonalmente à passarela foram posicionadas duas câmeras digitais no plano sagital. Os procedimentos fotogramétricos foram realizados pelo software Dvideow 6.3. O software Matlab 7.0.1 foi utilizado para filtrar e calcular as variáveis dependentes. O teste U de Mann-Whitney localizou diferenças para o tipo de paralisia cerebral para a extensão/hiperextensão do joelho (U = - 2,943; p= 0,003), no ângulo relativo do joelho no amortecimento (U = - 5,992; p= 0,001) e na amplitude do joelho na passada (U = - 4,099; p= 0,001). O teste t de Wilcoxon localizou diferenças quanto ao hemicorpo para os hemiplégicos apenas no ângulo relativo do joelho no amortecimento (T= - 2,635; p<0,008). As contribuições da amplitude de movimento passiva do joelho, reveladas pelas correlações de Spearman, para os diplégicos perna ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Capacidade motora; Paralisia cerebral nas crianças; Movimento (Educação física); Joelhos; Paralisia cerebral espástica; Spastic cerebral palsy